Prehospital versus in-hospital unfractionated heparin in ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention: a systematic review and meta-analysis - Yee-Jen Wu; Hung-Ju Lin; Yen-Hung Lin; Chi-Sheng Hung (European Journal of Emergency Medicine, 2026)
Background and importance In patients with ST-segment elevation myocardial infarction (STEMI), myocardial loss continues until coronary reperfusion is achieved. Objective To evaluate whether prehospital administration of unfractionated heparin (UFH) improves preprocedural infarct-related artery patency and clinical outcomes in patients undergoing primary percutaneous coronary intervention (PCI). Design Systematic review and meta-analysis. Electronic databases (PubMed, EMBASE, CENTRAL, and Web of Science) and clinical trial registries were systematically searched through March 2026. Settings and participants Patients with STEMI scheduled for primary PCI across seven included studies (two randomized controlled trials and five observational studies), totaling 10 954 participants, with 78.1% male patients. Intervention or exposure Prehospital UFH administration compared with PCI-capable hospital UFH administration. Outcome measures and analysis Prespecified endpoints included pre- and postprocedural thrombolysis in myocardial infarction (TIMI) flow grade, 30-day mortality, a composite endpoint of 30-day or in-hospital mortality, and major bleeding events. Main results Prehospital UFH was associated with a significantly higher rate of preprocedural TIMI 2–3 flow compared with control [odds ratio (OR): 1.49, 95% confidence interval (CI): 1.28–1.74; P < 0.001). Prehospital UFH was not associated with a significant reduction in 30-day all-cause mortality (OR: 0.70, 95% CI: 0.44–1.13; P = 0.141; I 2 = 60.9%), although a significant reduction was observed for the composite endpoint of 30-day or in-hospital mortality across all seven studies (OR: 0.68, 95% CI: 0.49–0.95; P = 0.023). Prehospital UFH was not associated with a significantly increased risk of major bleeding (OR: 0.77, 95% CI: 0.57–1.05; P = 0.099; I 2 = 0%). Conclusion In patients with STEMI undergoing primary PCI, prehospital UFH was associated with improved preprocedural coronary patency without an apparent increase in major bleeding. However, no statistically significant reduction was observed in 30-day mortality. Large-scale randomized controlled trials adequately powered for clinical endpoints are needed to establish the role of prehospital UFH in contemporary STEMI care.